The Femme-Masculinity in The Marjan Ramadan Advertising Series - Patricia, Yolanda; Lobodally, Altobeli (Talenta Publisher, 2024)
Femme-masculinity is a gender terminology to describe a woman who identifies herself between the feminine and masculine genders. This femme-masculine gender is represented in the Marjan Ramadan 2022 Ad Series Versions â€œMarjan, Bangkitkan Harapanâ€, â€œMarjan, Berbuka Penuh Harapanâ€, dan â€œMarjan, Rayakan Kemenanganâ€. This study aims to dismantle the representation of femme-masculinity in the Marjan Ramadan 2022 Ad Series Versions â€œMarjan, Bangkitkan Harapanâ€, â€œMarjan, Berbuka Penuh Harapanâ€, and â€œMarjan, Rayakan Kemenanganâ€. The theory used is Stuart Hallâ€™s Representation Theory, using a qualitative approach and Roland Barthesâ€™s Semiotic Analysis method, namely denotation, connotation, and myth. The results of this study found that femme-masculinity in Marjanâ€™s advertisements is represented as an androgynous figure, an intelligent figure, a heroic figure, a warrior figure, a leader figure, and a brave figure. Marjanâ€™s advertisements seem to represent a femme-masculine figure in their advertisements, but this is nothing more than just for profit. Thus, the representation of femme-masculinity in Marjanâ€™s Commercial Series is only a false reality.